Antioxidant substances of collection strains cyanobacteria Spirulina platensis (Experimental biology, 2015)
In article is considered results of investigation of productivity and pigment contents of the biomass of collectionstrains of cyanobacteria Spirulina platensis CALU 532 and Spirulina platensis ZBK-1. It is found that the strain S.рlatensis CALU 532 exceeds of the strain S. рlatensis by speed growth of cells and by exit of dry biomass. Quantity of dry biomass cyanobacteria S. platensis CALU 532 on 6-days total-4,1g/l, for S. platensis ZBK-1 this measure equal -2.3g/l. Investigation of maintenance of pigments in dry biomass researching of cyanobacteria showed that in biomass S.platensis ZBK-1 contents 0.58 mg/g carotenoids and 0.33 mg/g β-carotin, whereas for the culture S. platensis CALU 532 this number total 0.77mg/g and 0.45 mg/g, accordingly. It is established that content of phycobiliproteins also increasein biomass of collection strains S. platensis CALU 532 compare with S. platensis ZBK. Then, content phycocyanin in biomass of culture S. platensis CALU 532 higher on 5,3% and allophycocyanin on 4,4%.
Keywords: antioxidants; cyanobacteria; Zarruka; carotenoids; phycobiliproteins; phycocyanins